Drug delivery by TAT-technology - Grdiša, Mira (Array, 2008)
Summary: TAT technology is a biochemical technique for introduction of full-length peptides or proteins into cells. This process occurs in a rapid, concentration-dependent fashion that appears to be independent of receptors and transporters. It has broad implications in experimental systems for regulating intracellular processes and has the potential to be used in the development of new therapeutic strategies for cancer, infectious diseases, and development of vaccines. It has been shown that different forms of TAT-p27 protein can modulate the cell cycle of cultured cell lines, depending on the concentration and type of cells. Transfer of TAT-proteins/peptides use from cell culture systems to animal disease models has been slow, but the ability of TAT conjugates to protect mice against ischemia, inhibit tumor growth, and enhance gene delivery suggests that they offer wide ranging pharmaceutical applications for treating a whole range of diseases